Encapsulation-vitrification and encapsulation-dehydration cryopreservation of Cattleya labiata Lindley, a threatened Brazilian orchid - Galdiano, R. F. [UNESP]; Lemos, E. G.M. [UNESP] (International Society for Horticultural Science (ISHS), 2018)
Orchid populations have been decreasing due to habitat loss and over-collection for ornamental use. Consequently, there is an urgent need to conserve germplasm resources. Cryopreservation of the threatened orchid Cattleya labiata L. was successfully achieved using encapsulation-vitrification and encapsulation-dehydration cryopreservation methods. Protocorms, of 0.1 cm in diameter, developed from 2-months-old germinating seeds and encapsulated in sodium alginate-beads, were precultured in half-strength Murashige and Skoog liquid medium containing 0.4 M sucrose on a shaker (110 rpm) at 25°C for 24 h. For encapsulation-dehydration, beads were treated in the loading solution (2 M glycerol and 0.4 M sucrose in half-strength Murashige and Skoog liquid medium) for 20 min and then exposed to a sterile air-flow from the laminar air-flow cabinet for 0, 1, 2, 4 or 6 h. For encapsulation-vitrification, beads were treated in the loading solution for 20 min and then exposed to PVS2 solution (30% (w/v) glycerol, 15% (w/v) ethylene glycol and 15% (w/v) dimethyl sulfoxide in half-strength Murashige and Skoog liquid medium containing 0.4 M sucrose at pH 5.7) for 0, 10, 20, 30 and 40 min. Comparing the two methods tested, it was observed that regeneration of cryopreserved protocorms using encapsulation-dehydration was higher (42%) with 4 h dehydration in laminar airflow cabinet, whereas using the dehydration-vitrification procedure it was 27% after dehydration for 10 min in PVS2 solution. Seedlings developed from these methods did not show any abnormal characteristics of growth in vitro, and were successfully hardened in greenhouse showing 80% survival after 120 days of acclimatization.
Keywords: Ex vitro establishment; Germplasm conservation; Orchidaceae; PVS2